Bovine Herpesvirus-1 antibodies levels and associated Risk Factors in unvaccinated Dairy Herds from tropical wet weather, Ecuador - Hitler Cedeño-Sánchez; Brinner Burgos-García; Jhoana Zambrano-Aveiga; Marcia Jurado-Hidalgo; Patricia Zambrano-Moreira; María Lugo-Almarza; María Gabriela Farías; Francisco Angulo-Cubillán (Universidad del Zulia, 2022)
In order to determine the antibodies levels against Bovine Herpesvirus type 1 (BHV-1) and associated risk factors in unvaccinated dairy herds of tropical wet weather of Ecuador, an investigation was carried out in thirteen production units (PU), in the Chone Canton, Province of Manabí. The sample size was calculate by cluster sampling and the variables to be evaluated were antibodies levels frequency, age, sex, ocular or vulvovaginal lesions, breed and PU. One hundred eighty three blood samples were taken from the jugular or caudal vein and labeled for transfer to the laboratory. The tubes were centrifuged at 3,220 g for 15 minutes and the sera were transferred to Eppendorf tubes that once labeled were stored at –20°C until processing. Antibodies levels against HBV-1 were measured through of competitive ELISA technique, and calculated with simples statistical. The risk factors were estimated through the Odds ratio and relative risk, and the significance level through the Chi-square. The general antibodies levels frequency was 58.47 %. According age, 28.57 % in animals under two years old (yr.old) and 67.38 % for cattle over two yr.old. According to the sex, males showed 18.18 % and females 82.61 %. The determined risk factors (P<0.05) were age and sex, with a significant relative risk (P<0.05) of 3.31 and 2.32, respectively. The unvaccinated dairy herds of Western lowlands of Ecuador, have high antibodies levels frequency against BHV-1, with females over two yr.old at the highest risk of presenting infectious bovine rhinotracheitis (IBR).